Comparison of Dynamic Balance between East Java Puslatda Athletes with Plantar Fasciitis and without Plantar Fasciitis - Wicaksono Alim Budihartanto; Hening Laswati Putra; Indrayuni Lukitra Wardhani; Yudith Dian Prawitri; Rosy Setiawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lower extremity injuries are the most common cases of athlete’s injury. Sports athletes often experience perturbations that disturb their balance. Poor balance is associated with an increased risk of injury in athletes. Plantar fasciitis affects the biomechanics of the foot and impairs pressure distribution and balance during walking and running. To compare the dynamic balance between athletes with plantar fasciitis and without plantar fasciitis. This analytic observational with a cross sectional retrospective study design was performed on 101 athletes, aged 16-32 years. There were 49 male athletes and 52 female athletes have undergone dynamic balance checked with the star excursion balance test (SEBT) and plantar fasciitis examinations based on ultrasonography (USG) examination. There was no difference in the normalized SEBT value between the athlete’s group with plantar fasciitis and the athletes without plantar fasciitis, with p value for the anterior direction = 0.317, anterolateral = 0.215, lateral = 0.062, posterolateral = 0.180, posterior = 0.246, posteromedial = 0.354, medial = 0.409, and anteromedial = 0.245. In summary, there is no difference in the dynamic balance between athletes with plantar fasciitis and without plantar fasciitis. Further research is needed to determine the compensation mechanism in athletes with plantar fasciitis and specific exercises for different sport.